NONISOTHERMAL SIMULATION OF ELECTRODEPOSITION (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2022)
The simulation of electrochemical deposition is developed by using a non-isothermal model. The model consists of two parts; the first is a continuum part that simulates the transport of heat and mass and the voltage distributions, and the second is a stochastic noncontinuum part that simulates the bulk diffusion, surface diffusion, and adsorption of the particles. The finite element method is used to solve the differential-algebraic governing equations of the continuum part whereas the Kinetic Monte Carlo method is used to simulate the particle actions in the non-continuum part. The model is applied to the electrodeposition of Zn in ZnSO4 additive-free electrolyte. A comparison is made between the experimental and the simulated results including the surface morphology and the temperature distributions. The results indicated that the simulation model is very promising to be used for such a complicated process.